7-cordial labeling of standard graphs - Kanani, Kailas; Modha, Mita (International Journal of Applied Mathematical Research, 2014)
We contribute here some standard results for 7-cordial labeling. It has been proved that fans, friendship graphs,ladders, double fans, double wheels admit 7-cordial labeling.